2018
DOI: 10.24969/hvt.2018.81
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar versus unipolar energy in the surgical ablation of atrial fibrillation in patients with mitral valve surgery

Abstract: Objective: To evaluate the presence of sinus rhythm or atrial fibrillation (AF) in patients who had mitral valve surgery with concomitant surgical ablation of AF, by unipolar or bipolar radiofrequency. Methods: Adults patients who had mitral valve replacement or mitral valvuloplasty with concomitant surgical ablation of AF, either by unipolar or bipolar radiofrequency, were consecutively included between the 2008 and 2012. Surgery was done by conventional median sternotomy. Results: A total of 99 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Some studies showed that unipolar RF can achieve comparable rates of SR after 1-year follow up to bipolar ablation independent of cardiac surgical procedure and of type of AF [ 32 ]. On the other hand, other studies showed that the use of bipolar ablation is superior to the unipolar surgical ablation of patients undergoing mitral valve surgery [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that unipolar RF can achieve comparable rates of SR after 1-year follow up to bipolar ablation independent of cardiac surgical procedure and of type of AF [ 32 ]. On the other hand, other studies showed that the use of bipolar ablation is superior to the unipolar surgical ablation of patients undergoing mitral valve surgery [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Improved cardiac output and survival improvement are the major clinical advantages of sinus rhythm restoration in the management of AF combined with CABG [Gillinov 2005]. The success of BRA needs to be evaluated not only for sinus rhythm restoration achievement over time, but also for the improvement in the quality of life in cardiac patients with AF [Canale 2018]. BRA has the advantage of an auditory feedback signal from the console system, so the surgeon is able to assess whether the lesion has reached the entire thickness of the atrial wall [Canale 2018;Vural 2018].…”
Section: Discussionmentioning
confidence: 99%